PENGARUH BUDAYA KOREA (GENDRE MUSIK K-POP) TERHADAP GAYA HIDUP DI KALANGAN MAHASISWA PLS UNIVERSITAS RIAU KOTA PEKANBARU - Eldarmi Oktavia; Wilson Wilson; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is whether Korean Culture (K-Pop Music Genre) has an effect on Lifestyle Among PLS Students, Riau University, Pekanbaru City?. And are there differences in Korean Culture (K-Pop Music Genre) that affect the Lifestyle Among PLS Students, Riau University, Pekanbaru City based on gender and actor?. This study aims to determine the level of influence of Korean culture (K-Pop music genre) on the level of lifestyle among PLS students, Riau University, Pekanbaru City. And is there a difference which means that Korean Culture (K-Pop Music Genre) has an effect on Lifestyle Among PLS Students, Riau University, Pekanbaru City based on gender. The population in this study was the influence of Korean culture (K-Pop music genre) on style among PLS students, Riau University, Pekanbaru City, as many as 140 PLS students. The sampling technique in this study is the Random Sampling technique using the Slovin formula. The number of samples in this study were 59 students Pls. Collecting data that the authors obtained using documentation techniques, and questionnaires (questionnaire), which consists of 48 Lifestyle variables (Y) and 21 statements of Korean Culture variable (X). Data were obtained from respondents who found 20 students for the trial sample and 59 students for the research sample. After the questionnaire was tested, there were 6 invalid Lifestyle variables (Y) and 2 invalid Korean Culture variables (X), and the researcher discarded invalid statements. Based on the analysis that out of 59 respondents, 15 respondents (25%) were male, while 44 respondents (75%). This shows that most of the respondents are dominated by female respondents.Key Words: Korean Culture, Lifestyle, Students Pls